The Online Archive and the Internet Archive: Challenges and Stakes - BOUCHETA Rahmouna (International Journal of Social Communication, 2023)
The present study seeks to identify the Internet Archive, its goals, and the significance it provides to beneficiaries and scholars. It also emphasizes the importance of open archives and their diversity across Arab and European national archive websites that have lately acquired popularity. To investigate the most relevant studies on the topic, the study used a descriptive-analytical approach. The research revealed that internet archiving had the most important findings. In the face of information security risks and dangers, on the other hand, several firms strive to identify methods, preventative measures, and processes to fight security concerns. Their purpose is to perform the job of information security and safeguarding successfully, with an increased emphasis on assuring ongoing operations and supplying high-quality information. This attempt strengthens the reliability of the information presented. It improves the stability of organizations, allowing them to carry out their role in providing services, the majority of which are now automated.